Analisis Tanggung Jawab Otoritas Jasa Keuangan dalam Pelaksanaan Pengawasan Market Conduct pada Kegiatan Investasi di Indonesia - Adhiwangsa, Adryan Dzaki (Universitas Batanghari Jambi, 2024)
This research is an in-depth review concerning the responsibility of the Financial Services Authority (OJK) in overseeing market conduct in investment activities in Indonesia. Within the complexity of the financial market context, OJK's role in ensuring compliance with principles of ethics, integrity, and transparency becomes the primary focus. The research also highlights the role of market conduct supervision as a safeguard for investors and an effort to maintain fairness and equality in the investment market. The study outlines the current conditions of the investment market in Indonesia, including recent changes and trends. Challenges faced by OJK in executing the function of market conduct supervision, such as adapting to financial product and technological innovations, are also detailed in this analysis. The aim of this research is to provide a broad perspective on the role of OJK in market conduct supervision, and to offer crucial insights into the dynamics of the Indonesian investment market. The research methodology employed in this study is Normative Legal Research, also known as Doctrinal Law, which conceptualizes law as provisions written within legislation or as norms representing human behavior deemed appropriate. It is hoped that this analysis will contribute significantly to formulating policies and strategic steps aimed at enhancing the financial market's health and investor protection in Indonesia.